Predictors of Postoperative Acute Kidney Injury after Coronary Artery Bypass Graft Surgery - Ortega-Loubon,Christian (2018)
Abstract Objective: The aims of this study were to identify the risk factors associated with acute kidney injury (AKI) after isolated surgical revascularization with cardiopulmonary bypass and to develop a model to predict the appearance of postoperative AKI. Methods: A total of 435 adult patients who underwent primary isolated coronary artery bypass graft (CABG) surgery, from 2012 to 2016, in the Clinic University Hospital of Valladolid (Spain) were enrolled. AKI was defined according to the risk, injury, failure, loss, and end-stage (RIFLE) criteria. Data were collected from hospital electronic medical records. Multiple logistic regression analysis was used to identify risk factors. Results: The prevalence of AKI was 12.4%. Multivariate analysis identified age (odds ratio [OR], 1.056; 95% confidence interval [CI], 1.016-1.098; P=0.005), hypertension (OR, 3.078; 95% CI, 1.151-8.230; P=0.018), low ejection fraction (EF) (OR, 6.785; 95% CI, 2.080-22.135; P=0.001), estimated glomerular filtration rate (eGFR) (OR, 1.017; 95% CI, 1.005-1.028; P=0.014), EuroSCORE II (OR, 1.049; 95% CI, 1.004-1.096; P=0.033), and no intake of calcium-channel blockers (CCB) (OR, 4.892; 95% CI, 1.496-16.025; P=0.022) as risk factors for AKI. These risk factors were included in a model to predict postoperative AKI with an area under a receiver operating characteristic curve of 0.783±0.036 (95% CI, 0.713-0.854; P<0.0001). Conclusion: Age, hypertension, low EF, eGFR, EuroSCORE II, and no intake of CCB were independent risk factors for postoperative AKI. These factors provide an easy and accurate model to predict postoperative AKI in patients undergoing cardiac surgery.